Urgensi Analisis Kebutuhan Dalam Pelayanan Bimbingan dan Konseling Di Sekolah - Muhammad Rafiul Muiz; Wahidah Fitriani (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2022)
The purpose of this study is to find, study and further explore scientifically and theoretically, about the importance of the position and role of needs analysis, in order to maximize the process of guidance and counseling services in schools. Through this research, it will be explained scientifically about the reasons for the importance of needs analysis for the formulation of bk services in schools. It is hoped that later from this research a basic paradigm of thinking will emerge related to the urgency of analyzing the needs for bk services. This research is a literature study which is a study carried out through the collection of information and data on various sources derived from libraries, which is inseparable from the problem to be solved. The data that has been obtained is then analyzed by the content analysis method. Needs analysis plays a role in planning programs in the long term, short term and certain programs, as well as laying the foundation for the formulation of counseling service programs that will be carried out. The implementation of the needs analysis for students can be the basis for the formulation of guidance and counseling programs in schools, by conducting a needs analysis of students, teachers can formulate various guidance and counseling service programs appropriately. Keywords: The Urgency of Needs Analysis; Counseling Guidance Services